2019
DOI: 10.1038/s41598-019-47836-8
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Environments Interfere with Bone Marrow-Derived Macrophage Inflammatory Mediator Release, the TLR4 Pathway and Glucose Metabolism

Abstract: Macrophages may be a crucial aspect of diabetic complications associated with the inflammatory response. In this study, we examined how hyperglycaemia, a common aspect of diabetes, modulates bone marrow-derived macrophages (BMDMs) under an inflammatory stimulus. To perform this study, BMDMs from non-diabetic and diabetic (60 mg/kg alloxan, i.v.) male C57BL/6 mice (CEUA/FCF/USP-488) were cultured under normal (5.5 mM) and high glucose (HG, 25 or 40 mM) conditions and stimulated or not stimulated with lipopolysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 76 publications
0
53
0
9
Order By: Relevance
“…Studies in other vertebrates demonstrate that high glucose exposure results in an increased cytokine response of macrophages upon lipopolysaccharide exposure but reduces the overall phagocytic rate (47, 48). Our data provides evidence that there is a high glucose concentration in the central organs (brain and liver) of Pachón cavefish in all treatment groups (Fig 4), which leads us to the hypothesis that high glucose concentration is the main driver of the hypersensitivity and reduced phagocytic rate of innate immune cells including macrophages in Pachón cavefish (36).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in other vertebrates demonstrate that high glucose exposure results in an increased cytokine response of macrophages upon lipopolysaccharide exposure but reduces the overall phagocytic rate (47, 48). Our data provides evidence that there is a high glucose concentration in the central organs (brain and liver) of Pachón cavefish in all treatment groups (Fig 4), which leads us to the hypothesis that high glucose concentration is the main driver of the hypersensitivity and reduced phagocytic rate of innate immune cells including macrophages in Pachón cavefish (36).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that lineage (29) and peritoneal macrophages (30) cultured under high glucose conditions tend to present M2-like phenotype characteristics, which would polarize them toward an adaptive rather than an innate immune response, and other studies relate the impaired phagocytic ability in AM of diabetic rats to reduced phosphorylation of ERK, Akt, and PKC-d resulting from deficient bonding of leukotrienes to FcgR signaling pathways (31). In addition, Ayala et al show that high glucose levels appear to modify macrophage behavior, affecting different aspects of diabetic (impaired phagocytic ability, reduced production of reactive hydrogen species, and reduced expressions of TLR-4 on the cell surface) and healthy bone marrow-derived macrophages under the same LPS stimulus, hypothesizing that hyperglycemia leaves a glucose legacy, altering the basal steady state of macrophages (32). More recently, Tessaro et al (33) also showed that in vitro treatment with insulin is able to amplify inflammatory cytokine secretion by bone marrow-derived macrophages from diabetic mice stimulated with LPS by enhancing phosphorylation of MAPK (p42 MAPK, p44 MAPK, p46 SAPK, p54 SAPK) resulting from TLR-4 activation with LPS, and mice deficient of mechanisms related to detection and phagocytosis, such as expressions of TLR-2 and TLR-4, were observed to be more susceptible to PCM (10).…”
Section: Discussionmentioning
confidence: 99%
“…The rats (n=48) were randomly divided into four groups (n=12 rats each) ( 36 , 37 ): i) Saline control group; ii) LPS (cat. no.…”
Section: Methodsmentioning
confidence: 99%